Investigating Phatic Particles ‘geh’ and ‘weh’ Used by the Younger Generation in Lampung - Sari, Puspita; Nugraha, Muhammad Arsyi Yuki; Rahman, Muhammad Wildan Fauzia; Haikal, Muhammad Said; Ishlah, Rafy Muhammad; Safanigara, Yuki Aldira Puteri (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research is entitled “Investigating Phatic Particles ‘geh’ and ‘weh’ Used by the Younger Generation in Lampung”. Observations of the spoken variety of Indonesian have not been widely carried out and not as many as observations of the written variety. The particles of geh and weh are widely used in the oral variety, but not many have done detailed research on these two particles. This research aims at investigating (1) in what sentences the phatic particles 'geh' and 'weh' are used by the younger generation in Lampung and (2) the functions and positions of the phatic particles ‘geh’ and ‘weh’ used by the young generation in Lampung. The method used is descriptive qualitative method. Meanwhile, the research techniques used were immersion, recovery, and permutation techniques with the steps as follows: identifying the phatic particles, classifying based on types of sentences, functions, and positions, analyzing the data based on types of sentences, functions, and positions, and concluding them based on the result of analysis. The data are collected from the conversations of young generation in Lampung from social media such as Twitter and Whatsapp. The research shows that these particles ‘geh’ and ‘weh’ are found in declarative, interrogative, and imperative sentences with final and medial positions. The geh particle is not found at the initial position and the weh particle is not found in medial position in imperative sentence. Related to their functions, both particles ‘geh’ and ‘weh’ have 3 (three) functions when used in conversation such as (1)having the aim of livening up the conversation and atmosphere, (2) generally presenting in the oral (conversation) mode and in the written form which is non-official, and (3) having the function of affirming a word or sentence.